2010
DOI: 10.1111/j.1365-263x.2010.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the sialochemistry, oral pH, and oral health status of down syndrome children to healthy children

Abstract: DS may manifest itself in the salivary glands. Consequently, different electrolyte salivary environment may form, leading to lower caries rates among DS children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 23 publications
5
85
1
6
Order By: Relevance
“…Whole saliva from ten healthy individuals (six females, four males) with a mean age of 56 ± 11 years (range, 40-68 years) was collected into sterile tubes according to the widely used protocol for the collection of saliva (Davidovich et al 2010). Subjects with any conditions/lesions that affect the oral cavity (i.e., infectious, autoimmune, pre-malignant and malignant) were excluded following a thorough examination by a specialist in oral medicine (AZH).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Whole saliva from ten healthy individuals (six females, four males) with a mean age of 56 ± 11 years (range, 40-68 years) was collected into sterile tubes according to the widely used protocol for the collection of saliva (Davidovich et al 2010). Subjects with any conditions/lesions that affect the oral cavity (i.e., infectious, autoimmune, pre-malignant and malignant) were excluded following a thorough examination by a specialist in oral medicine (AZH).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Low prevalence of dental caries or tooth decay in both primary and permanent dentitions of DS individuals has been widely reported (Cutress, 1971a;Orner, 1975;Barnett et al, 1986;Vigild, 1986;Ulseth et al, 1991;Gabre et al, 2001;Bradley & McAlister, 2004;Cheng et al, 2007;Dellavia et al, 2009;Davidovich et al, 2010). Cutress (1971a) examined 416 DS subjects and found lower prevalence of dental caries than normal population, but after adjusting the age of teeth eruption, there were only small and no significant difference between 2 groups.…”
Section: Dental Cariesmentioning
confidence: 99%
“…Various studies have shown a reduced prevalence of caries in DS children when compared with unaffected children Bradley & McAlister, 2004;Cogulu et al, 2006;Davidovich et al, 2010). It has been reported that young DS children had prolonged use of bottle as a result of feeding problems or behavioral difficulties, with increased risk of developing nursing bottle caries (Randell et al, 1992) (Figure 7).…”
Section: Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…These higher prevalence relating periodontal diseases cannot only be explained by poor oral hygiene alone and may be the result of impaired immune responses and deficient phagocytic systems (Morinushi et al, 1997). Dental caries susceptibility is usually low in those with Down syndrome (Davidovich et al, 2010). Cleidocranial dysplasia (osteodentin dysplasia) has dental significance.…”
Section: Local and Systemic Factors That Influence Tooth Eruptionmentioning
confidence: 99%